Navigating Cultural and Linguistic Boundaries Online: A CAT-Based Analysis of a Multicultural Gaming Discord Community in Southeast Asia - Victoria Janae Supit (Jogjakarta Communication Conference (JCC), 2026)
Online multiplayer games such as Valorant provide dedicated servers for Southeast Asian players, creating spaces where individuals from different regions regularly interact and collaborate toward shared in-game objectives. Many of these players extend their interactions beyond the game through Discord, forming communities that bridge geographical and cultural boundaries. While research on online communication has grown considerably, informal multicultural communities remain understudied, particularly in the Southeast Asian context. As technology continues to evolve, the study of intercultural communication has yet to be fully expanded to the digital realm, leaving questions about how cultural adjustments unfold online largely unaddressed. This study investigates communication accommodation patterns within a small Valorant Discord community comprising Indonesian, Malaysian, and Filipino members. Drawing on netnography and Communication Accommodation Theory (CAT), data were collected through participant observation and semi-structured interviews. Analysis followed an abductive approach, combining inductive thematic coding with deductive interpretation through CAT's framework of adjustment strategies. Findings reveal that members employ a range of accommodation strategies when navigating linguistic and cultural differences in this informal digital space. English emerges as the community's primary convergence strategy, functioning as both a communicative tool and a mechanism for social inclusion. Members also develop supplementary strategies including conscious and unconscious adoption of each other's linguistic expressions and mannerisms. However, accommodation is not uniform — native language use under emotional pressure or during co-national exchanges produces moments of non-accommodation and communicative exclusion. These findings extend CAT's application to a Southeast Asian digital gaming context, contributing to understandings of intercultural communication in informal online communities.